2017
DOI: 10.1248/bpb.b16-00688
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Microbial Contamination in Multiple-Dose Preservative-Free Ophthalmic Preparations

Abstract: Multiple-dose ophthalmic preparations that do not contain preservatives carry high risks of microbial contamination. However, there are various types of hospital preparations, with different physicochemical properties. In the present study, we evaluated the association between physicochemical properties and microbial contamination in ophthalmic preparations. The investigated hospital preparations included ophthalmic preparations of physiological saline, 0.2% fluconazole, 0.5% vancomycin hydrochloride, and 2% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…Their small size can make gripping and squeezing difficult, especially in patients with tremor or arthritis of the hands. Some of these obstacles can be overcome with multidose preservative-free formulations, but these are at risk of microbial contamination [ 103 ]. Systems to prevent microbial influx into multidose preservative-free formulations—such as the proprietary ABAK and COMOD systems—have been developed and are available for a limited number of drugs [ 3 ].…”
Section: Approaches To Minimize or Eliminate Bak Toxicitymentioning
confidence: 99%
“…Their small size can make gripping and squeezing difficult, especially in patients with tremor or arthritis of the hands. Some of these obstacles can be overcome with multidose preservative-free formulations, but these are at risk of microbial contamination [ 103 ]. Systems to prevent microbial influx into multidose preservative-free formulations—such as the proprietary ABAK and COMOD systems—have been developed and are available for a limited number of drugs [ 3 ].…”
Section: Approaches To Minimize or Eliminate Bak Toxicitymentioning
confidence: 99%
“…However, a large volume of eye drops packages (more than 5 ml) for multiple uses of medicines does not always allow maintaining the sterility of the solution for a long time if there are no preservatives in the composition itself [23].…”
Section: Preservatives In Eye Drop Technologymentioning
confidence: 99%
“…In two reports of contamination of preservative-free hospital-prepared eye drops, 8.4% 4 and 16.7% 1 were found to be contaminated, and the bottles used by patients at home were more tainted than those used by medical staff in inpatient settings. 4 , 5 Another study showed there was no difference between contamination rates in eye drops administered by staff in outpatient departments and those instilled in wards using shared medications in multi-user settings; however, inter-patient transmission of microorganisms could have influenced the results.…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that without preservatives, ophthalmic solutions may become contaminated. 1 It is possible that microbial contamination may alter the pH of preparations and reduce the eye drops' efficacy. 2 , 3 Therefore, maintaining sterility during eye drop use is a crucial measure.…”
Section: Introductionmentioning
confidence: 99%